Åarjelsaemien gïele goh dïhte jillemes uralske gïele jïh akte gieltegs dotkemeobjeekte - Jussi Ylikoski (Nordlyd, 2023)
The article discusses the role and importance of South Saami, the westernmost language of the westernmost branch of the Uralic language family, in Saami, Uralic as well as general typological linguistics. It briefly summarizes the origins of the South Saami language and discusses some of the most prominent characteristic features of the language in its Saami and Scandinavian contexts. Special attention is given to three phenomena: 1) the so-called relation forms of nouns, etymologically related to the comparative marking of adjectives, but synchronically reminiscent of markers of definiteness and possession; 2) differential object marking with as many as three distinct morphological cases (accusative, nominative and elative); and 3) the nature and origins of the auxiliary verb edtjedh ‘shall’, possibly a degrammaticalization of the Proto-Saami potential mood marker.